Digital Contact Tracing, Privacy, and Public Health. Issue 3 (29th June 2020) - Martinez‐Martin, Nicole; Wieten, Sarah; Magnus, David; Cho, Mildred K.
Abstract: Digital contact tracing, in combination with widespread testing, has been a focal point for many plans to "reopen" economies while containing the spread of Covid‐19. Most digital contact tracing projects in the United States and Europe have prioritized privacy protections in the form of local storage of data on smartphones and the deidentification of information. However, in the prioritization of privacy in this narrow form, there is not sufficient attention given to weighing ethical trade‐offs within the context of a public health pandemic or to the need to evaluate safety and effectiveness of software‐based technology applied to public health .